Muscle Stretching Education at Mazaya Leather Shoes Home Industry in RW 11 Sukaregang, Wetan City Village, Garut District, Garut Regency. - Iwan Shalahuddin; Udin Rosidin; Mamat Lukman; Ahmad Yamin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Health education was chosen as an intervention for Mazaya Leather Industrial Home employees because information is fundamental to achieving goals such as safety, health, and ergonomics management. According to the study's findings, in order to produce a more successful muscle stretching intervention, a strategy of information transmission and attention on the impact caused must be used. The goal of the service is to identify potential issues and how to solve them independently in the Mazaya Leather Sukaregang Home Industry, Wetan City Village, Garut Kota District. The approach used in health education is an explanation or lecture delivered by a speaker to workers and home industry owners about stretching muscles between tasks. Results: learning requirements. It is clear that some workers have learning needs that are included in learning needs: perceived needs, unperceived needs, and misperceived needs. This is because some participants are aware of the dangers of not preventing work risks with good and correct stretching, which is harmful to their health. Number of attendees: 10 persons, which will take place on Monday, February 12, 2024 at 10 a.m. - WIB will be completed immediately. The audience consists of workers from all aspects of the shoemaking industry. Conclusion: The counseling participants appeared excited when the content was presented. Participants enjoyed the therapy since it was carried out in a positive manner. Counseling activities were beneficial because participants paid close attention to the content delivered.